A new species of Eugenia (Myrtaceae) from Rio de Janeiro State, Brazil - Mazine, Fiorella F.; Sobral, Marcos; Valdemarin, Karinne Sampaio (Phytotaxa, 2018)
A new species of Eugenia from Atlantic forest of Rio de Janeiro State is described, illustrated, and discussed. Eugenia circumdata is characterized by its inflorescences with tomentose, brown-yellowish indumentum, bracteoles orbiculate or obovate, concave, surrounding the flower bud, and deciduous at anthesis. Eugenia circumdata is most similar to Eugenia myrobalana, from which it differs mainly by its smaller leaf blades, axillary inflorescences, and shorter pedicels. Moreover, the species described here is known only from collections in Reserva Biológica União, in the municipality of Rio das Ostras. Data on its conservation status are presented.